Eksistensi Hukum Islam dalam Sistem Hukum Nasional: (Kedudukan, Peran Lembaga Negara, dan Dinamika Pengembangannya) - Andi Silva Quadsajul; Riska Amalia Ramadani; Andi Maharani Erwin; Kurniati Kurniati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The existence of Islamic law within the Indonesian legal system continuously transforms alongside the dynamics of legal politics and contemporary societal needs. Although constitutionally not a theocratic state, Indonesia with its Muslim-majority population persistently integrates Sharia values into its regulations and judicial system. Utilizing statutory, conceptual, and historical approaches, this normative juridical research aims to analyze the position of Islamic law, the contribution of state institutions to its legislation and enforcement, as well as the dynamics of its development through policies and judicial decisions. The study finds that Islamic law holds a strategic position as a pillar in the formulation of national law. Legislative and law enforcement institutions, such as the House of Representatives (DPR), the President, the Supreme Court (MA), the Constitutional Court (MK), and the Religious Courts, play a crucial role in aligning Islamic law with constitutional principles. This dynamic is evidenced by the emergence of various regulations and court rulings that blend the essence of Sharia with human rights and the principles of a democratic state ruled by law. Therefore, synergy and harmonization between Islamic law and national law must be continuously strengthened to foster a just and adaptive legal system.